2020
DOI: 10.31943/gemawiralodra.v11i2.136
|View full text |Cite
|
Sign up to set email alerts
|

Rancang Bangun Sistem E-Marketing Dalam Meningkatkan Pemasaran Umkm (Usaha Mikro, Kecil Dan Menengah) Di Kabupaten Indramayu

Abstract: Menurut Kepala Diskopdagin Kabupaten Indramayu Trisna Hendarin mengakui, pelaku UMKM (Usaha Mikro, Kecil dan Menengah) di Kabupaten Indramayu pemasarannya masih minim maka dilakukan pembuatan Rancang Bangun Sistem E-Marketing dalam Meningkatkan Pemasaran UMKM (Usaha Mikro, Kecil dan Menengah). Tujuan di adakan penelitian ini adalah untuk mengatasi masalah pemasaran yang dialami oleh industri rumahan dan memberikan kontribusi kepada kelompok UMKM (Usaha Mikro, Kecil dan Menengah) untuk menerapkan E-Marketing. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…I price summarize the habit of Indonesians online shopping based on the data impression from google analytics during February and March 2020. Digital Based Marketing used to gain costumers, building preferences, and brand promotion, maintaining costumer, and increase selling that leads to profit (Sari et al, 2020) Shopping interest on Polygon brand is increased 1036% since the early March 2020 compared to February. Not only in Indonesia, the trend of buying indoor and outdoor bicycle is also occurred in England, as the BBC reported that there has been a 15% increase of the bicycle buying.…”
Section: Figure 1 Trends In the Search For Bicycle Models In Indonesiamentioning
confidence: 99%
“…I price summarize the habit of Indonesians online shopping based on the data impression from google analytics during February and March 2020. Digital Based Marketing used to gain costumers, building preferences, and brand promotion, maintaining costumer, and increase selling that leads to profit (Sari et al, 2020) Shopping interest on Polygon brand is increased 1036% since the early March 2020 compared to February. Not only in Indonesia, the trend of buying indoor and outdoor bicycle is also occurred in England, as the BBC reported that there has been a 15% increase of the bicycle buying.…”
Section: Figure 1 Trends In the Search For Bicycle Models In Indonesiamentioning
confidence: 99%